Genetic alterations of epithelial polarity genes are associated with loss of polarity in invasive breast cancer. Issue 6 (30th October 2019) - Catterall, Rachel; Lelarge, Virginie; McCaffrey, Luke
Abstract : Breast cancer remains a leading cause of cancer‐related death for women. The stepwise development of breast cancer through preinvasive to invasive disease is associated with progressive disruption of cellular and tissue organization. Apical–basal polarity is thought to be a barrier to breast cancer development, but the extent and potential mechanisms that contribute to disrupted polarity are incompletely understood. To investigate the cell polarity status of invasive breast cancers, we performed multiplex imaging of polarity markers on tissue cores from 432 patients from a spectrum of grades, stages and molecular subtypes. Apical–basal cell polarity was lost in 100% of cells in all cases studied, indicating that loss of epithelial polarity may be a universal feature of invasive breast cancer. We then analyzed genomic events from the TCGA dataset for an 18‐gene set of core polarity genes. Coamplification of polarity genes with established breast oncogenes was found, which is consistent with functional cooperation within signaling amplicons. Gene‐expression levels of several polarity genes were significantly associated with survival, and protein localization of Par6 correlated with higher grade, nodal metastasis and molecular subtype. Finally, multiple hotspot mutations in protein–protein interaction domains critical for cell polarity were identified. Our data indicate that genomic events likely contribute to pervasive disruption of epithelial polarity observed in invasive breast cancer. Abstract : What's new? Epithelial cell polarity is a barrier to cancer progression yet, mechanisms that disrupt polarity remain poorly understood. The authors demonstrate loss of cell polarity is a ubiquitous feature of invasive breast cancers, independent of subtype, grade, stage, and tumor type. Diverse genetic events including co‐amplification with oncogenes and 3D hotspot mutations in protein–protein interaction domains essential for epithelial polarity. This study identifies genomic events that likely contribute to disrupted cell polarity in invasive breast cancers.